Self - Realization & The Religious Representation of The ‘Other’ in the Islamic Studies Textbooks - Ramdane, Tahraoui; Souad, Merah (2019)
This paper aims to explore the nature of the values and modes of their transmission in the Islamic Studies Textbooks (IST) used by Secondary school students at the International Islamic School Malaysia (IISMS). It also aims to investigate how these values reinforce students’ self- understanding and self-realization vis-à-vis the religious representation of the Other. It also aims to investigate whether these values create a world view tainted by tolerance and co-existence or foster a feeling of rupture, mistrust and enmity. A ‘Content Analysis Model’ was developed based on little john’s (1998) textbook analysis model. Besides two other models were designed based on Patrick R. Moran’s (2001) Teaching Culture Perspectives. These two models consist of ‘Religious Knowing Model’ used to analyze self-realization and ‘Religious Representation of the Other Model’ employed to analyze the representation of the Other. The subject of analysis in this study is the Islamic Studies textbook used at the 7th, 8th and the 9th grades for the academic year 2019-2020. The findings have shown that these textbooks create both tolerant or intolerant trends among Muslim students through the depiction of the Other. They also show that there is a meager presence of civic values such as tolerance, moderation and coexistence. As for the religious representation of the Other, the findings show that it was secondary to religious correctness showcasing, self-glorification and realization. It is believed that this study will help understand the causes of alienation Muslim students feel vis-a-vis non-Muslims. It will also explain the role of Islamic Studies syllabus in shaping Muslim students’ views towards themselves. Besides it will assist teachers and those who are responsible or concerned about Islamic education curriculum to realize that, there is a dire need to write up to -date Islamic Studies textbooks by taking into consideration the current social reality of life and treat students as global citizens and not to confine them to their group of believers only.